A Critical Appraisal of China’s ‘Four Comprehensives’ Grand Narrative - John Garrick; Yan Chang Bennett (UUM Journal of Legal Studies, 2015)
In China today,President Xi Jinpingâ€™s new grand narrative is framed by the widely publicised â€˜four comprehensivesâ€™ (å››ä¸ªå…¨é¢; â€˜sigequanmianâ€™). This narrative aims to : 1.build a moderately prosperous society; 2. deepen reform; 3. govern the nation according to law, and 4. tighten Party discipline. It is essentially a political narrative that tells a moral tale that legitimizes and glorifies the virtues of the present. It also attempts to shrug off mistakes of the previous dynasty. Drawing on the legal disciplines of economic law, international comparative law and the a priori analytic method of legal narrative analysis, this paper provides a critical appraisal of the â€˜four comprehensivesâ€™, paying special attention to how the four principal strands of the narrative shape the directions of Chinaâ€™s socialist rule of law reforms and governance.